They will (not) deceive us! The role of agentic and communal national narcissism in shaping the attitudes to Ukrainian refugees in Poland. (July 2023) - Nowak, Bartłomiej; Brzóska, Paweł; Piotrowski, Jarosław; Żemojtel-Piotrowska, Magdalena; Jonason, Peter K.
Abstract: Even though Poles accept war refugees from Ukraine, the refugees could represent a realistic threat (via economic competition), which could create anti-refugee attitudes. However, they are unlikely to represent a symbolic threat toward ingroup values, given that they are culturally like Poles. Agentic and communal national narcissists differ in their sensitivity toward realistic and symbolic threats but agentic ones are more sensitive to realistic threats whereas communal ones react more to symbolic ones. Therefore, we expect their different reactions toward Ukrainian refugees along with accepting relevant justifications of such reactions, that is, Russian anti-Ukrainian narration. Therefore, we examined ( N  = 402) the attitudes of Polish national agentic and communal narcissists toward Ukrainian refugees, both directly and indirectly, through belief in Russian narration. Agentic national narcissism was associated with less favorable attitudes toward Ukrainians both directly and indirectly through stronger beliefs in Russian narration. Communal national narcissism was correlated with more favorable attitudes toward Ukrainians and weaker beliefs in Russian narration. The results align with the idea that national narcissists react stronger to the kind of threat relevant to the domain that satisfies their narcissistic needs. Therefore, national narcissism is not necessarily accompanied by more anti-refugee prejudice. Highlights: Agentic national narcissism (NN) is related to higher anti-Ukrainian prejudice. Communal NN is related to lower anti-Ukrainian prejudice. Accepting Russian narration mediates the link between NN and prejudice. Results point to sensitivity of agentic NNs to realistic but not to symbolic threats.